MSW A Potential Energy Resources: A Two Stage Anaerobic Digestion - Paranjpe, Archana; Sharma, Abhay Kumar; Ranjan, R. K.; Paranjape, Vishal (Asian Journal of Science and Applied Technology, 2021)
Present investigation reveals the biodegradability of municipal solid wastes (MSW) in context of Jabalpur city [1] (at 23˚10 North latitude and 79˚57 East longitude, at an altitude of 393 meters above mean sea level) and harnessing energy through two stage anaerobic digestion. A critical study of various process parameters affecting the anaerobic digestion has been analyzed. During the anaerobic digestion of MSW it has been seen that the retention time of the process increases as compared to other waste such as fruits and vegetable waste, cow dung, agricultural residues etc. With the use of suitable bio-methanization technology the twin objectives (a) waste reduction and (b) the environmental problems can be achieved. The present work will help all academicians, rural and urban energy industry people in generating eco-friendly energy and maintaining environment too. In this study the biodegradability of the MSW organic fraction has been tested and in particular a comparison between the production of biogas from landfills and organic wastes in anaerobic conditions has been performed. Two stage digestion of this kind of wastes were proved a better efficiency than single stage digestion.